2020
DOI: 10.1149/1945-7111/ab6c5b
|View full text |Cite|
|
Sign up to set email alerts
|

An Analysis of Solid-State Electrodeposition-Induced Metal Plastic Flow and Predictions of Stress States in Solid Ionic Conductor Defects

Abstract: The use of inorganic solid-ionic conductors with a metal electrode, has been proposed as a way to increase energy density, decrease capacity loss and prevent failure from metal propagation. Current observations of Li-metal electrodes causing cell shorting in solid-state systems have been identified as main obstacles limiting the development of this technology. However, many aspects of the involved phenomenon have not been fully addressed theoretically. In this work, we derive a mathematical model of electrodep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
82
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(83 citation statements)
references
References 52 publications
0
82
1
Order By: Relevance
“…In addition, high ionic conductivity has been shown to limit pressure build up in the SE and may therefore favorably influence resistance against Li penetration. 217 More superionic conductors are likely to be discovered given the improved understanding of alkali-ion conductivity 218−223 and the large number of discovery projects going on worldwide. 224−229…”
Section: Opportunities For Solid-state Batteriesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, high ionic conductivity has been shown to limit pressure build up in the SE and may therefore favorably influence resistance against Li penetration. 217 More superionic conductors are likely to be discovered given the improved understanding of alkali-ion conductivity 218−223 and the large number of discovery projects going on worldwide. 224−229…”
Section: Opportunities For Solid-state Batteriesmentioning
confidence: 99%
“…287,288 The use of a Li metal anode results in additional issues of contact loss during plating/stripping, possible interfacial reactions, and Li propagation through the conductor. 214,215,217,289 Most of these mechanical and chemical interfacial instabilities increase the overpotential, resulting in lower energy density and capacity fade. Finally, practical cells will also require very thin SE separators that are easily processed and handled, and high cathode loading, which are issues that have only been partially addressed so far by the scientific community.…”
Section: Challenges Facing Assbsmentioning
confidence: 99%
“…20 Finally, interface and surface roughness has also been identified as a crucial factor dictating filament nucleation and growth. 21 Recently, a few experimental studies have suggested that lithium filament growth is affected by stack pressure. 10,14,17 The latter result suggests that non-uniform contact upon electrochemical cycling may be a significant driver for filament growth.…”
mentioning
confidence: 99%
“…It is generally hypothesized that the ability of a Li filament to nucleate and propagate is dependent on the fracture toughness of the electrolyte. 11,[28][29][30] Additionally, the strains associated with cathode particle expansion or the strain associated with interphase formation have been shown to be sufficient to fracture the solid electrolyte. 7,8,31 The dynamic nature of the interface poses further restrictions on the mechanical properties of coatings and interlayers, which must also be sufficiently tough to avoid fracture.…”
Section: Mechanical Behavior Of the Solid Electrolytementioning
confidence: 99%
“…Although earlier models for describing electro-chemo-mechanical phenomena in SSBs only considered the elastic response of the Li metal, the recent increase in experimental measurements have aided the development of models to account for the complexities of both elastic and plastic behavior, as illustrated by the examples in Figure 2. For example, a work by Barroso-Luque et al 30 developed a model to predict the magnitude of internal pressures generated by Li electrodeposition into a Griffith-like flaw. Barai et al 37 studied the impact of inhomogeneity (grain boundaries) on Li penetration in LLZO, accounting for both elastic and plastic deformation of the Li (Figure 2D).…”
Section: Mechanical Behavior Of LI Metal and Interfacesmentioning
confidence: 99%